PENYUTRADARAAN NASKAH SULTAN THAHA SAIFUDDIN KARYA EM. YOGISWARA BERBASIS TEATER TRADISI DUL MULUK - saputra, medi (Tonil: Jurnal Kajian Sastra, Teater dan Sinema, 2017)
Adapting a legendary folklore into the role play is absolutely very contradiction with public watcher nowdays. Society dominantly has chosen to watch movies or another television programs that makes theatre’s becoming retarded. It caused of globalization effect and technology development which more sophisticated day by day. Afterwards, a creative idea as a play director was turning up that has a responsibility for making a play to readapt norms and moral values which had been left behind. Dul Muluk, as one of traditional role plays that had been a basic play director processing in a theatre with the title Sultan Thaha Saifuddin from EM. Yogiswara. Sultan Thaha Saifuddin is a heroic person from Negeri Jambi and the last king from Kesultanan Tanah Pilih Kampung Gedang Jambi. His heroic, firm and wise makes Jambi society support him consistently and solidly to avoid the Netherland. In adapting this legendary folklore, the writer was collecting the data as references from earlier works about Dul Muluk theatre and its development, also the supporting stories about the legend of Kesultanan Melayu Jambi. The data was found and involved for making a modern theatre that can be accepted by the society nowdays. Keywords: People Struggling, Sultan Thaha, Dul Muluk, Play Director, Theatre